Granitos do tipo-A (1,38-1,30 Ga) relacionados com a evolução do sistema orogênico Rondoniano-San Ignacio, SW Craton Amazônico, Brasil: Uma revisão geoquímica - Leite Júnior, W. B. [UNESP]; Payolla, B. L.; Bettencourt, J. S.; Tavares Dias, C. A. [UNESP] (My University, 2014)
Two main groups of A-type or ferroan granitoids (1.38- 1.30 Ga) related to the development of the Rondonian-San Ignacio Province (1.56-1.30 Ga) are recognized in the Rondônia Tin Province: alkalic metaluminous granitoids and alkali-calcic metaluminous granitoids with or without associated peraluminous granitoids. The first group includes the granitoids of the Teotônio Intrusive Suite, and the second one includes the granitoids of the Santo Antonio, Alto Candeias, and São Lourenço-Caripunas intrusive suite. These suites are interpreted to be related to episodic extensional regime in a within-plate tectonic setting. We believe that the alkalic metaluminous granitoids were formed by fractional crystallization of ferro-basalt parent magma, whereas the alkalicalcic metaluminous granitoids were crystallized from anatectic melts derived from quartzo-feldspathic sources in response to mafic underplating.
1.38-1.30 ga a-type granites related to the evolution of the rondonian-san ignacio orogenic system, SW amazonian craton, Brazil: A geochemical overview
Keywords: A-type granite; Geochemistry; Rondonian Tin Province; SW Amazonian Craton